Gender and Islam in Southeast Asia : women's rights movements, religious resurgence and local traditions - Schröter, Susanne, 1957- (Women and Gender: The Middle East and the Islamic World, 2013)
The volume is the first comprehensive compilation of texts on gender constructions, normative gender orders and their religious legitimizations, as well as current gender policies in Islamic Southeast Asia, which besides the Islamic core countries of Malaysia and Indonesia also comprises southern Thailand and Mindanao (the Philippines). The authors trace the impact of national development programmes, modernization, globalization, and political conflicts on the local and national gender regimes in the twentieth century, and elaborate on the consequences of the revitalization of a conservative type of Islam. The book, thus, elucidates the boundary lines of cultural and political processes of negotiation related to state, society, and community. It employs a broad analytical framework, offers rich empirical data and gives new insights into current debates on gender and Islam. Contributors include Nelly van Doorn-Harder, Farish A. Noor, Siti Musdah Mulia, Amporn Marddent, Maila Stivens, Alexander Horstmann, Amina Rasul-Bernardo, Monika Arnez, Susanne Schröter, Nurul Ilmi Idrus, Vivienne S.M. Angeles and Birte Brecht-Drouart.